The effects of different cryopreservation conditions on feline peripheral blood mononuclear cells (PBMCs) viability - Azhar, Siti Aisyah (2016)
Peripheral blood mononuclear cells (PBMCs) contain immune cell subsets such as lymphocytes and monocytes. Characterisation of their immune functions are pertinent in providing fundamental information on its mechanism and response. In this study, the temperature and composition of cryopreservation media were examined to determine the effects on feline PBMCs viability. Blood samples were obtained from 15 healthy cats and feline PBMCs were isolated using density gradient centrifugation technique. The PBMCs were stored in -196°C for 2 weeks in cryopreservation media of three different conditions; namely, 10% DMSO with 90% FBS, 10% DMSO with 90% feline serum (FS) and the combination of 10% DMSO with 45% FBS and 45% FS. In addition, two different temperatures (4°C and room temperature) of cryopreservation media were assessed. The cell viability was measured by using trypan blue dye exclusion technique and viability staining using flow cytometry. The result from dye exclusion technique showed that the addition of FS provide a similar recovery of feline PBMCs immediately upon thawing as compared to the utilization of FBS. However, the result from flow cytometric analysis revealed a higher PBMCs viability when using FS as compared to FBS. In addition, different cryopreservation medium temperature did not provide significant recovery of feline PBMCs after cryopreservation.Overall, the use of FS in cryopreservation media has provided comparable feline PBMCs recovery compared to FBS immediately upon thawing. In addition FS may play a role in maintaining feline PBMCs viability. However, their role in the clinical endpoints of other assays could not be excluded.